Business cycle dependent unemployment insurance - Torben M. Andersen; Michael Svarer (Institute for the Study of Labor (IZA), 2010)
The consequences of business cycle contingencies in unemployment insurance systems are considered in a search-matching model allowing for shifts between good and bad states of nature. We show that not only is there an insurance argument for such contingencies, but there may also be an incentive argument. Since benefits may be less distortionary in a recession than a boom, it follows that counter-cyclical benefits reduce average distortions compared to state independent benefits. We show that optimal (utilitarian) benefits are counter-cyclical and may reduce the structural (average) unemployment rate, although the variability of unemployment may increase.
Keywords: J6; H3; 330; unemployment benefits; business cycle; insurance; incentives; Arbeitslosenversicherung; Konjunkturelle Arbeitslosigkeit; Arbeitsplatzsuchmodell; Theorie